EKSISTENSI BIMBINGAN KARIR DI DESA DAN KOTA DALAM PEMILIHAN KARIR SISWA - Salim, Agus; Fadhilah, Sinta Rahmatil; Aminah, Siti; Yuanita, Yuanita; Al-Havis, Muhammad; Malika, Tetra; Qamarah, Metra Arifin (Universitas Al-Amien Prenduan, 2024)
This research examines the role of guidance and counseling in high school, focusing on the importance of the role of guidance and counseling teachers in helping students understand themselves and their environment. The method used is a qualitative descriptive approach through observation, interviews, and documentation in several high schools in Jambi. The research results show that career guidance is a crucial component in school guidance and counseling programs. This program plays an important role in helping students achieve optimal personal and academic development. However, many high school students face big challenges in choosing a career path, especially in deciding to continue their college education. Effective guidance and counseling can be a solution to help students overcome these obstacles and make the right decisions regarding their future. This research emphasizes the important role of guidance and counseling in supporting student development in school and provides insight into the need to strengthen career guidance programs in the context of secondary school education.